Effects of Naphthaleneacetic Acid and Kinetin on Chrysanthemum Plantlets in Vitro - Saipul Sihotang; Magdalena Saragih; Swati Sembiring; Riduan Sembiring; Dini Puspita Yanty; Denny Akbar Tanjung; Elli Afrida (Green Engineering Society, 2025)
Naphthaleneacetic acid (NAA) and kinetin play a crucial role in plant growth but must be used in correct proportions in order to produce the best outcomes. An optimal combination of both can enhance shoot, leaf, and root growth, whereas inappropriate doses may otherwise inhibit growth due to hormonal imbalance. This study examined the effects of the interaction between NAA and kinetin on the growth of chrysanthemum plants at eight weeks of age. The research was carried out using the Completely Randomized Design (CRD) in triplicate. The medium used was MS medium, supplemented with NAA at concentrations of 0–1.5 mg/L and kinetin at concentrations of 0–3 mg/L. The results indicate that NAA and kinetin positively influenced plant growth, but only when the optimal concentrations were applied. The best combination of NAA at 1.0 mg/L (N2) and kinetin at 3.0 mg/L (K3) produced the best results in terms of height (153 mm), number of leaves (31 leaves), number of roots (26 roots), and fresh weight (5.85 g). Increasing kinetin concentrations (K0-3) generally promoted plant growth, whereas excessive NAA concentrations (> 1.0 mg/L, N3) produced the opposite effect, likely due to toxicity or hormonal imbalance. The interaction between kinetin and NAA exhibited a synergistic effect up to a certain threshold, while excessive NAA application negatively impacted on plant development.